Melting heat transfer in a nanofluid boundary layer on a stretching circular cylinder - Gorla, Rama Subba Reddy; Chamkha, Ali J.; Al-Meshaiei, Eisa (Journal of Naval Architecture and Marine Engineering, 2012)
A boundary layer analysis is presented for the warm, laminar nanoliquid fluid flow to a melting cylindrical surface moving parallel to a uniform stream. The resulting system of non-linear ordinary differential equations is solved numerically using Runge-Kutta method with shooting techniques. Numerical results are obtained for the velocity, temperature and concentration distributions, as well as the friction factor, local Nusselt number and local Sherwood number for several values of the parameters, namely, the Reynolds number, Prandtl number and nanofluid parameters. The obtained results are presented graphicallyand in tabular form and the physical aspects of the problem are discussed. DOI: http://dx.doi.org/10.3329/jname.v9i1.7416 Journal of Naval Architecture and Marine Engineering 9(2012) 1-10